Critical Review of Technology-Based Education Supervision Models: Implications for Improving The Quality of Learning in The Digital Age - Lisa Handayani; Rita Lebang; Sutono; Fajar Eriza Rikasari; Warman (JPP (Jurnal Pendidikan dan Pembelajaran), 2024)
This study aims to conduct a critical review of the technology-based educational supervision model and its implications for improving the quality of learning in the digital era. This model integrates conventional supervision concepts with digital technologies to provide more effective support to educators in the development of their teaching practices. In this study, we conducted an examining pertinent literature to pinpoint the effectiveness, challenges, and potential of technology-based educational supervision models. Positive implications of this model include greater accessibility to supervision and guidance for educators, flexibility of time and place, and increased efficiency in providing feedback. However, challenges such as inadequate technology infrastructure, security and data privacy concerns, and the absence of instruction in utilizing technology may hinder successful implementation.